2020
DOI: 10.21203/rs.3.rs-130882/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sofosbuvir-Upregulated Genes Facilitate The Development of Hepatocellular Carcinoma

Abstract: Background: Direct-acting antivirals (DAAs) have achieved a sustained virological response (SVR) rate of 95-99% in treating HCV. Several studies suggested that treatment with sofosbuvir (SOF) containing DAAs may be associated with increased risk of developing HCC. The aim of this study is to investigate the potential mechanisms of SOF on the development of HCC.Methods: This study used OR-6 (harboring full-length genotype 1b HCV) and Huh 7.5.1 cells to examine the effects of SOF on cell proliferation and migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(69 reference statements)
1
1
0
Order By: Relevance
“…The finding of basilar hyperplasia in Subgroup IIA in this study is in agreement with [38] that proved that SOF upregulates several genes that were associated with increased cell proliferation and migration.…”
Section: Loss Of Basilar Polarity Observed In Subgroupsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding of basilar hyperplasia in Subgroup IIA in this study is in agreement with [38] that proved that SOF upregulates several genes that were associated with increased cell proliferation and migration.…”
Section: Loss Of Basilar Polarity Observed In Subgroupsupporting
confidence: 92%
“…In this study, the presence of Ki67 in the deep layers of the epithelium suggests that despite cell loss from the surface by desquamation, cell division and apoptosis seemed to be disturbed. Other investigators have reached the same results and found that SOF was disturbing the regulation of cell proliferation, which may lead to apoptosis [38,50,51] who suggested that the use of DAADs can affect cellular proliferation especially on grafted tissues. This is also in agreement with these studies that suggests SOF cause overproduction of (ROS) which leads to disorder of metabolism, degeneration of organelles and cell death by apoptosis [23,29,35,41] .…”
Section: Loss Of Basilar Polarity Observed In Subgroupmentioning
confidence: 67%